Development of the Italian version of the trunk impairment scale in subjects with acute and chronic stroke. Cross-cultural adaptation, reliability, validity and responsiveness. Issue 1 (2nd January 2019) - Monticone, Marco; Ambrosini, Emilia; Verheyden, Geert; Brivio, Flavia; Brunati, Roberto; Longoni, Luca; Mauri, Gaia; Molteni, Alessandro; Nava, Claudia; Rocca, Barbara; Ferrante, Simona
Abstract: Purpose: To cross-culturally adapt and psychometrically analyse the Italian version of the Trunk Impairment Scale on acute ( cohort 1 ) and chronic stroke patients ( cohort 2 ). Methods: The Trunk Impairment Scale was culturally adapted in accordance with international standards. The psychometric testing included: internal consistency (Cronbach's alpha), inter- and intra-rater reliability (intraclass correlation coefficient; standard error of measurement and minimal detectable change), construct validity by comparing Trunk Impairment Scale score with Barthel Index, motor subscale of Functional Independence Measure, and Trunk Control Test (Pearson's correlation), and responsiveness (Effect Size, Effect Size with Guyatt approach, standardized response mean, and Receiver Operating Characteristics curves). Results: The Trunk Impairment Scale was administered to 125 and 116 acute and chronic stroke patients, respectively. Internal consistency was acceptable (α > 0.7), inter- and intra-rater reliability (ICC > 0.9, Minimal Detectable Change for total score < 1.6 in cohort 1 and < 1.1 in cohort 2 ) were excellent. The construct validity showed acceptable correlations ( r  > 0.4) with all scales but the motor Functional Independence Measure in cohort 2 . Distribution-based methods showed large effects in cohort 1 and moderate to large effects in cohort 2 . The Minimal Important Difference was 3.5 both from patient's and therapist's perspective in cohort 1 and 2.5 and 1.5 from patient's and therapist's perspective, respectively, in cohort 2 . Conclusion: The Trunk Impairment Scale was successfully translated into Italian and proved to be reliable, valid, and responsive. Its use is recommended for clinical and research purposes. Implications for Rehabilitation: Trunk control is an essential part of balance and postural control, constituting an important prerequisite for daily activities and function. The TIS administered in subjects with subacute and chronic stroke was reliable, valid and responsive. The TIS is expected to help clinicians and researchers by identifying key functional processes related to disability in people with subacute and chronic stroke.